Effect Of Bioijuk Density On Decreasing TSSIn Sail River Water - Prisusan Permata Hati; Budijono Budijono; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Sail River is one of the Siak watersheds that have been polluted due to high levels of TSS. This study aims to determine the level of reduction in TSS levels by using different bioijuk densities. This research was conducted in March-April 2019. The method used was a completely randomized design (CRD), which was used as treatment, was bioijuk density. P¬1 (infrequent density), P2 (medium density) and P3 (meeting density), and 3 replications. The sampling location is selected in the inlet and outlet area. The results of the measurement of the average reduction in the highest TSS levels were found in P2, 207 mg / L with a reduction in effectiveness (EP) of 97%. From the results of the study, it was known that the density of different bioijuk did not significantly influence the decrease in TSS, levels in the Sail River water.Keywords : Bioijuk, Continuous Solids, Dissolved Solids, Turbidity, Bacteria